Development of polymer based multi-function nanocomposite coating system / Ammar Shafaamri - Ammar , Shafaamri (2018)
In this study, polymer-based nanocomposite coating systems were developed based on the utilization of a hybrid acrylic–silicone polymeric matrix and two types of nanoparticles, namely, SiO2 and ZnO, at different loading rates of 1 wt. %, 3 wt. %, 5 wt. % and 8 wt. %. Then, by modifying the base acrylic–silicone polymeric matrix with various loadings of epoxy resin and epoxidized soybean oil, fully organic coating system were prepared and investigated. All developed coating systems were subjected to the same conditions in the curing process, using polyisocyanate (NCO) as the curing agent. The brush method was used to apply the developed coating system onto the surface of the pretreated cold-rolled mild steel substrates. To fully cure and dry, all prepared samples were kept at room temperature for seven days and all the coated films were controlled to have a dry-film thickness of 75 ±5 mm. The ability of the developed single-layer coating system for use in multifunctional coating films was confirmed via the utilization of various characterization techniques in order to evaluate different properties of the developed coating systems. The properties investigated included the chemical structure, surface morphology, wettability, transparency, thermal stability, adhesion performance and corrosion protection ability. The obtained results reveal that a nanoparticle loading ratio of 3 wt. % for both SiO2 and ZnO can be considered to be the optimum ratio as it provides the most pronounced enhancement of the overall coating performance especially for the corrosion protection and barrier properties. Also, a significant improvement was obtained by introducing 9 wt. % of epoxy resin and 1 w. % of epoxidized soybean oil to the acrylic–silicone polymeric blend. These results conclusively confirm that the coating system with 3 wt. % SiO2 nanoparticles (AS 3) demonstrates the best overall performance and successful multifunctionality.